HOME EXPERIMENT TO DETERMINE THE SPECIFIC HEATS CP/CV RATIO FOR AIR - Podlasov, Serhii; Snarskii, Andrei (Physical and Mathematical Education, 2024)
Formulation of the problem. Future engineers need to be able to conduct experimental research and process their results. In the conditions of distance learning, teachers face the problem of developing tasks for experimental research that students can perform at home using available equipment. One such research task can be determining the adiabatic index of a gas based on the results of measuring the speed of sound.Materials and Methods. To achieve the research objective, we used the analysis of the curriculum of the course "General Physics for Bachelors of Engineering", a review of the methodological instructions for performing laboratory work in the section "Oscillations and Waves" of the physics course of technical universities, and a review of the literature on the research topic. The prepared equipment and software made it possible to test the methodology for determining the air adiabaticity index by the sound speed found in the experiment.Results. The speed of sound was calculated using the resonant frequency values for tubes of different lengths, as well as the body of a ballpoint pen, a cylindrical vessel (tea mug), and a bottle, which can be considered Helmholtz resonators to some extent. As it turned out, for reliable fixation of the resonant frequency in the tubes open at both ends, it is advisable to use the pulse-modulated sound frequency generator (PMSG) created by us as a sound source. For exciting sound in a bottle, both the PMSG and a technique similar to playing the flute can be used.Conclusions. Home experiments conducted with various objects used as resonators (a bottle, tubes of different lengths, a cup) allowed us to obtain values of the speed of sound in air ranging from 334 m/s to 352 m/s and a corresponding adiabatic index of 1.33 ≤ γ ≤ 1.45. This can be considered a sufficiently good estimate for air when conducting home experiments.
Keywords: Home experiment; speed of sound; speed of sound; specific heats ratio CP/CV